Culture- and metagenomics-enabled analyses of the Methanosphaera genus reveals their monophyletic origin and differentiation according to genome size. Issue 12 (December 2018) - Hoedt, Emily; Parks, Donovan; Volmer, James; Rosewarne, Carly; Denman, Stuart; McSweeney, Christopher; Muir, Jane; Gibson, Peter; Cuív, Páraic; Hugenholtz, Philip; Tyson, Gene; Morrison, Mark
Abstract The genusMethanosphaera is a well-recognized but poorly characterized member of the mammalian gut microbiome, and distinctive fromMethanobrevibacter smithii for its ability to induce a pro-inflammatory response in humans. Here we have used a combination of culture- and metagenomics-based approaches to expand the representation and information for the genus, which has supported the examination of their phylogeny and physiological capacity. Novel isolates of the genusMethanosphaera were recovered from bovine rumen digesta and human stool, with the bovine isolate remarkable for its large genome size relative to otherMethanosphaera isolates from monogastric hosts. To substantiate this observation, we then recovered seven high-qualityMethanosphaera -affiliated population genomes from ruminant and human gut metagenomic datasets. Our analyses confirm a monophyletic origin ofMethanosphaera spp. and that the colonization of monogastric and ruminant hosts favors representatives of the genus with different genome sizes, reflecting differences in the genome content needed to persist in these different habitats.